2018
DOI: 10.1111/joa.12767
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical models of human cerebellar development in the fetal period

Abstract: The evaluation of cerebellar growth in the fetal period forms a part of a widely used examination to identify any features of abnormalities in early stages of human development. It is well known that the development of anatomical structures, including the cerebellum, does not always follow a linear model of growth. The aim of the study was to analyse a variety of mathematical models of human cerebellar development in fetal life to determine their adequacy. The study comprised 101 fetuses (48 males and 53 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
7
0
2
Order By: Relevance
“…The study excluded fetuses with visible developmental malformations and those that did not have complete clinical documentation. The reliability and scientific value of the collection used for research have been confirmed in many previously published studies (14)(15)(16)(17)(18)(19)(20)(21). Basic data of the studied fetus population have been presented in Table (Table I).…”
Section: Methodsmentioning
confidence: 54%
“…The study excluded fetuses with visible developmental malformations and those that did not have complete clinical documentation. The reliability and scientific value of the collection used for research have been confirmed in many previously published studies (14)(15)(16)(17)(18)(19)(20)(21). Basic data of the studied fetus population have been presented in Table (Table I).…”
Section: Methodsmentioning
confidence: 54%
“…Fetuses with visible developmental malformations and those that did not have complete clinical documentation were excluded from the study. The value of the fetal collection was confirmed in numerous previously published scientific studies (27)(28)(29)(30)(31)(32)(33). The scientific experience of the team has been confirmed in many works using anatomical scientific methodology and anatomical techniques used for statistical analysis (34)(35)(36).…”
Section: Methodsmentioning
confidence: 66%
“…While these branches are fascinating for anatomists, they are also of great clinical importance. Their unusual localization may lead to unpredictable complications, especially as it is likely that, in addition to the sensory fibers, they may also conduct motor fibers to musculus peroneus tertius (29) or musculus extensor digitorum brevis (43).…”
Section: Discussionmentioning
confidence: 99%
“…The value and credibility of the fetal collection has been confirmed in many scientific papers [15,16,[23][24][25][26]. The basic characteristics of the study material are presented in Table 1.…”
Section: Methodsmentioning
confidence: 86%
“…The results of the measurements were analyzed statistically on the basis of Statistica PL statistical package (Statsoft, Tulsa, USA). The statistical analysis was carried out by an experienced statistician with high mathematical skills documented and confirmed in previous analyses [23,30].…”
Section: Methodsmentioning
confidence: 99%